The association of prothrombin A19911G polymorphism with plasma prothrombin activity and venous thrombosis: Results of the MEGA study, a large population-based case-control study - Y. Chinthammitr (2018)
Background: Prothrombin (FII) G20210A mutation and elevated plasma prothrombin activity are known risk factors for venous thrombosis. The risk of venous thrombosis among 19911G carriers of the prothrombin A19911G polymorphism has not been extensively investigated. Objectives and methods: We assessed prothrombin activity, FIIG20210A, and FIIA19911G polymorphisms in a large population-based case-control study, the Multiple Environmental and Genetic Assessment (MEGA) study of risk factors for venous thrombosis. Four thousand three hundred and sixty-five consecutive patients with a first episode of deep vein thrombosis of the leg or pulmonary embolism were included. The control group (n = 4779) consisted of partners of patients or persons gathered using a random-digit dialing method. We studied the effect of FIIA19911G polymorphism on prothrombin activity and thrombosis risk, also in combination with factor V Leiden. Results: Among FII20210-GG control subjects, FII19911-GG carriers had 7.1% [95% confidence interval (CI): 5.7-8.5] higher mean prothrombin activity than FII19911-AA carriers and the risk for GG carriers was 1.43-fold increased compared to AA carriers [odds ratio (OR) 1.43; 95% CI: 1.27-1.61]. Among FII20210-GA control carriers, the mean prothrombin activity in both FII19911-AA and -AG carriers was nearly equivalent [131.7% and 133.4%; mean difference (95% CI)=1.7% (-7.2-10.7)]. Because of genetic linkage, FII19911-GG carriers were very rare on a FII20210-GA background, as only one FII20210A carrier had FII19911-GG. In FII20210-GA carriers, the OR increased from 3.05 (95% CI: 2.17-4.27) in subjects with FII19911-AA to 3.33 (2.28-4.85) in subjects with FII19911-AG, compared to those with FII20210-GG and FII19911-AA. Conclusions: The FIIA19911G polymorphism is associated with mildly elevated prothrombin activity and is a risk factor for venous thrombosis. © 2006 International Society on Thrombosis and Haemostasis.